Diagnostic diagrams for the classification of galactic nuclei: comparison of traditional and alternative diagrams - Aydar, Catarina Pasta (2021)
The central region of galaxies might present much higher surface brightness than the other parts of the host galaxy. A supermassive black hole resides in this region, and there can also be gas and stars. The main goal of this work is to improve the tools that are used to classify the activity in the nuclei of galaxies. We want to determine more precisely if what is causing the emission in the nuclear region of each galaxy is the activity associated to star formation or to the growth of the central black hole. In view of that, we use a sample with 4 192 spectral observations of nearby galactic nuclei and propose diagrams that allow us to separate those that are ionized by stars from those that are ionized by the accretion of matter onto a supermassive black hole. We also run models of gas being ionized by this two possible sources of energy to better understand the usefulness of the diagnostic diagrams we are proposing. We describe this study with a review about the classification of galactic nuclei, and we propose new tools that collaborate to the refinement of such field.